Aversive Counterconditioning Attenuates Reward Signaling in the Ventral Striatum - Kaag, Anne Marije; Schluter, Renée S.; Karel, Peter; Homberg, Judith; van den Brink, Wim; Reneman, Liesbeth; van Wingen, Guido A. (Frontiers in Human Neuroscience, 2016)
Appetitive conditioning refers to the process of learning cue-reward associations and is mediated by the mesocorticolimbic system. Appetitive conditioned responses are difficult to extinguish, especially for highly salient rewards such as food and drugs. We investigate whether aversive counterconditioning can alter reward reinstatement in the ventral striatum in healthy volunteers using functional Magnetic Resonance Imaging (fMRI). In the initial conditioning phase, two different stimuli were reinforced with a monetary reward. In the subsequent counterconditioning phase, one of these stimuli was paired with an aversive shock to the wrist. In the following extinction phase, none of the stimuli were reinforced. In the final reinstatement phase, reward was reinstated by informing the participants that the monetary gain could be doubled. Our fMRI data revealed that reward signalling in the ventral striatum and ventral tegmental area following reinstatement was smaller for the stimulus that was counterconditioned with an electrical shock, compared to the non-counterconditioned stimulus. A functional connectivity analysis showed that aversive counterconditioning strengthened striatal connectivity with the hippocampus and insula. These results suggest that reward signalling in the ventral striatum can be attenuated through aversive counterconditioning, possibly by concurrent retrieval of the aversive association through enhanced connectivity with hippocampus and insula.